2023
DOI: 10.3390/ijms241411766
|View full text |Cite
|
Sign up to set email alerts
|

Esaxerenone Inhibits Renal Angiogenesis and Endothelial-Mesenchymal Transition via the VEGFA and TGF-β1 Pathways in Aldosterone-Infused Mice

Abstract: Renal fibrosis is an inevitable process in the progression of chronic kidney disease (CKD). Angiogenesis plays an important role in this process. Vascular endothelial cells are involved in renal fibrosis by phenotypic transformation and secretion of extracellular matrix. Aldosterone stimulates mineralocorticoid receptor (MR) activation and induces inflammation, which is important for angiogenesis. Clinically, MR blockers (MRBs) have a protective effect on damaged kidneys, which may be associated with inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Esaxerenone, which is a new non-steroidal MR antagonist, improves endothelial dysfunction caused by diabetes by promoting eNOS phosphorylation in the DCM group [5,6]. Several clinical studies have reported that esaxerenone has significant antihypertensive and cardiorenal protective effects compared with spironolactone and eplerenone [7,8]. Pharmacological studies have shown that due to its inverted side-chain structure, esaxerenone has an affinity for MRs that is over 1000 times higher than other NR3C nuclear receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Esaxerenone, which is a new non-steroidal MR antagonist, improves endothelial dysfunction caused by diabetes by promoting eNOS phosphorylation in the DCM group [5,6]. Several clinical studies have reported that esaxerenone has significant antihypertensive and cardiorenal protective effects compared with spironolactone and eplerenone [7,8]. Pharmacological studies have shown that due to its inverted side-chain structure, esaxerenone has an affinity for MRs that is over 1000 times higher than other NR3C nuclear receptors.…”
Section: Introductionmentioning
confidence: 99%